Monitoring voltage stability in power system - Mat Yunus, Nor Asiah; Ramli, Nur Mardiana; Ismail, Nor Hayati (Jurnal Penyelidikan Sains Sosial, 2025)
Voltage stability continues to be a challenge for the power grid in Malaysia, as demand increases, and renewable sources enter the mix. This paper aims to explain the method developed a real-time stability monitoring algorithm, offering a Voltage Stability Index (VSI) integrating PV and QV analysis and transient dynamics. The algorithm is coded in MATLAB and evaluates stability over power factors (0.8 lag to 0.9 lead) on a test system that's a modified IEEE 14-bus system incorporating Malaysian characteristics. Simulations exhibit a runtime of 0.08 seconds—150 times faster than continuation power flow achieving an ~85% success rate on collapse prediction. Combined PV and QV curves validate performance for normal, outage, and renewable surge conditions, detecting instability at as low as 50%-65% loading, better than current methods' lower thresholds. Light, flexible, this solution fits the real-time requirement of Malaysia with potential future implementations incorporating machine learning and actual grid data for extensive deployment, lending itself to support sustainable energy aims.